2021
DOI: 10.3390/cimb44010014
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in B Cell and Follicular T-Helper Cell Subsets in Patients with Acute COVID-19 and COVID-19 Convalescents

Abstract: Background. Humoral immunity requires interaction between B cell and T follicular helper cells (Tfh) to produce effective immune response, but the data regarding a role of B cells and Tfh in SARS-CoV-2 defense are still sparse. Methods. Blood samples from patients with acute COVID-19 (n = 64), convalescents patients who had specific IgG to SARS-CoV-2 N-protein (n = 55), and healthy donors with no detectable antibodies to any SARS-CoV-2 proteins (HC, n = 44) were analyses by multicolor flow cytometry. Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Thus, altered B cell activation in circulation and vitamin D deficiency could be associated with an increased risk of autoimmune disorders and poor outcomes of infectious diseases. Finally, an increased level of activated B cells and altered B cell subset composition was detected in the peripheral blood of patients recovered after COVID-19 [55,56]; thus, future studies will be needed to investigate whether supplementation with regular vitamin D can prevent or reduce the risk of developing severe pathologies associated with 'post-COVID' syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, altered B cell activation in circulation and vitamin D deficiency could be associated with an increased risk of autoimmune disorders and poor outcomes of infectious diseases. Finally, an increased level of activated B cells and altered B cell subset composition was detected in the peripheral blood of patients recovered after COVID-19 [55,56]; thus, future studies will be needed to investigate whether supplementation with regular vitamin D can prevent or reduce the risk of developing severe pathologies associated with 'post-COVID' syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that decreased B cell counts in the acute stage of COVID-19 are related to the impairment of their maturation at the level of antigen-independent differentiation. Furthermore, B cell subset alterations could persist for at least several months after the acute stage of the disease [ 35 ]. Such long-term impairment of adaptive humoral immunity may be closely associated with an increased risk of a wide range of autoimmune disorders [ 36 , 37 ], the incidence of which dramatically increases after COVID-19 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…B cells are classified based on surface CD27 and CD38 expression into transitional (CD27 - CD38 ++ ), naïve (CD27 - CD38 + ), plasmablasts (CD27 ++ CD38 + ), memory unswitched (IgD + CD27 + CD38 - ), memory switched (IgD - CD27 + CD38 - ), and double-negative cells (CD27 - CD38 - ) ( 240 ). The prototypical B cell response to a viral infection features an initial extrafollicular (EF) B cell signature, which involves the differentiation of naive B cells into plasmablasts that generate low-affinity and temporary antibodies.…”
Section: Adaptive Immune Response Against Sars-cov-2mentioning
confidence: 99%